Analysis Of Islamic Education Values In Punakawan Puppet Characters - Khusnul Ariyanto; Rustam Ibrahim (Sean Institute, 2024)
The use of wayang as a learning medium is carried out through storytelling activities. Please note that wayang here is not in a physical sense, but in a non-physical form. The teacher simply tells puppet stories that contain good values and teaches the characters of the puppet characters for students to emulate, for example the story about Yudistira, the eldest brother of the Pandavas, who was wise, responsible and had the spirit of a leader. Through this wayang story, students can learn various wayang characters that are appropriate to those that are not worthy of being emulated while also cultivating knowledge about Indonesian cultural treasures. The focus of this research is 1) How the characters of the Punakawan wayang are in wayang 2) How to analyze the values of Islamic education in the characters of the Punakawan wayang. This research uses qualitative research with the type of literature review research or often called library research. So in collecting data using primary data sources and secondary data. Data collection techniques use Desktop Research, Documentation Study. Meanwhile, the analysis technique is carried out by means of discussion material based on a literature review of works, whether in the form of books or other readings related to this writing. Punakawan puppets consist of semar, gareng, petruk, bagong. Whereas from respectively figure the have character individually. Semar have character in wayang, namely: respected by friends and foes alike, Semar is a respected figure, but remains humble, not arrogant, honest and still loves others. Gareng has a character in wayang: a person who is not good at talking, what he says is sometimes awry but he is very funny and ridiculous. Petruk has a character in wayang: mischievous and intelligent, sweet-faced with a smile that dances to the heart, good at talking, very funny, likes to insinuate untruths with his jokes. Bagong has deep character wayang: likes to joke when facing very serious problems, sassy, likes to act stupid, very funny.